Bio e-Nose for Virgin Coconut Oil (VCO) Standardization - Mohd Noor, Ahmad; Ali Yeon, Md Shakaff; Mohd Yusoff, Mashor; Zulkafli, Daud; Solhan, Yahya; Anas, Mohd Noor; Azman, Mat Hussin; Suhardy, Daud (Malaysian Invention and Design Society (MINDS), 2010)
Mohd Noor Ahmad and his team from School of Bioprocess Engineering won bronze for Bio e-Nose for Virgin Coconut Oil (VCO) Standardization. ITEX 2006, 19th - 21st May 2006 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.